Implementasi metode bermain peran untuk melatih kemampuan komunikasi verbal anak disabilitas intelektual - Galih Fajar Fadillah; Dinda Rahma Putri; Angga Eka Yuda Wibawa; Anni Nurul Hidayati (Journal of Profession Education, 2025)
Children with intellectual disabilities often experience significant barriers to verbal communication, including difficulties speaking, understanding messages, and participating in conversations. These problems impact their ability to establish social interactions and express their needs. This research aims to describe how the role-playing method is implemented to train verbal communication skills in children with intellectual disabilities. This study employed a qualitative, descriptive approach. Data were collected through observation, in-depth interviews, and documentation. The research subjects consisted of one teacher and four students with mild intellectual disabilities at the junior high school level, selected through purposive sampling. Data validity was established through triangulation techniques. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results demonstrate that the role-playing method was implemented through eight systematic stages: scenario development, instruction, role selection, demonstration, activity implementation, guidance and reinforcement, post-activity discussion, and evaluation. This learning process helped children become more courageous in speaking, imitate simple expressions, and respond to conversation partners more effectively. These findings demonstrate that role-playing can be an appropriate learning approach for children with intellectual disabilities in the context of verbal communication training. Furthermore, this method proved effective in building confidence and encouraging active participation in learning activities.